Patterns of Use and Self-reported Effectiveness of Cannabis for Hyperemesis Gravidarum - First, Olivia K.; MacGibbon, Kimber W.; Cahill, Catherine M.; Cooper, Ziva D.; Gelberg, Lillian; Cortessis, Victoria K.; Mullin, Patrick M.; Fejzo, Marlena S. (Geburtshilfe und Frauenheilkunde, 2022)
Introduction There is limited research on effective treatment of Hyperemesis Gravidarum (HG), the most extreme version of nausea and vomiting during pregnancy (NVP). This paper examines current patterns of use and self-reported effectiveness of cannabis/cannabis-based products (CBP) to treat HG.Materials/Methods The study employed a 21-question survey to gather information on demographics, antiemetic prescription use, and experience with cannabis/CBPs among individuals who experienced extreme nausea and vomiting or HG during their pregnancy. Age-adjusted unconditional logistic regression was used to compare odds of symptom relief and weight gain between respondents who used prescription antiemetics and those who used cannabis.Results Of the 550 survey respondents, 84% experienced weight loss during pregnancy; 96% reported using prescription antiemetics and 14% reported cannabis use for HG. Most respondents reported using cannabis/CBPs (71%) because their prescribed antiemetics were self-reported to be ineffective. More than half of cannabis/CBP users reported using products daily or multiple times per day (53%), primarily via smoke inhalation (59%), and mainly either delta-9-tetrahydrocannabinol (THC) only or THC dominant preparations (57%). Eighty-two percent of cannabis/CBP users reported symptom relief, compared to 60% of prescription antiemetic users. Among patients who reported weight loss during pregnancy, 56% of cannabis users reported gaining weight within two weeks of treatment, compared to 25% of prescription antiemetic users.Conclusions Respondents reported using cannabis primarily because prescribed medications were self-reported to be ineffective. Although the survey approach has inherent limitations so results should be interpreted with caution, in this sample, cannabis was self-reported to be more effective than prescription medications in alleviating HG symptoms and enabling pregnancy weight gain. Therefore, depending on the safety profiles, randomized, double-blinded, placebo-controlled trials of cannabis compared to other antiemetics are warranted to determine whether cannabinoids may provide an effective alternative treatment for HG.
Keywords: hyperemesis gravidarum; cannabis; pregnancy